Anthropogenic stable cesium in water and sediment of a shallow estuary, St. Louis Bay, Mississippi. (5th May 2015) - Bera, Gopal; Yeager, Kevin M.; Shim, MooJoon; Shiller, Alan M.
Abstract: St. Louis Bay (SLB), Mississippi, is a small, shallow estuary with moderate local residential and industrial development. Dissolved, stable Cs (i.e., 133 Cs) was significantly enriched in bay waters (up to 1570 nM) as compared to river (<1 nM) and ocean waters (2.3 nM). A TiO2 refinery, located on the north shore of the bay, is the likely source of the Cs, given that the highest Cs concentrations were found in waters and in surface sediments (up to 49 μg/g) near the refinery outfall. This setting presented a unique opportunity to study remobilization of Cs in a shallow estuarine system, where sediment resuspension is frequent. Remobilization (up to ∼3 fold increase) of dissolved Cs was observed during sediment resuspension events. A weak correlation between Cs and clay %; strong correlations among Cs, silt % and particulate organic carbon (POC); and simple numerical approaches indicate that desorption from resuspended particulate matter is the likely mechanism of Cs remobilization. Cs-enriched SLB waters can be traced to nearshore Mississippi Sound waters, but not into Mississippi Bight waters further offshore. The findings from this study also suggest that caution needs to be taken when interpreting the radio-cesium distribution in shallow estuarine and coastal systems. Highlights: Cs enrichment was observed in waters and some sediments of a Mississippi bay. The Cs enrichment appears tied to the outfall of a TiO2 refinery. Sediment resuspension/desorption caused increased water column Cs concentrations. Coastal water near the bay had a small Cs enrichment, but not water further offshore. Results indicate the mobility of Cs in estuarine environments.